GE_GERICHTE C/643/2017 vom 12. November 2018 - GE Cour de justice (2018)
MAXIME DES DÉBATS ; BAIL À LOYER ; DROIT D'ÊTRE ENTENDU ; LOCATAIRE DE REMPLACEMENT | CPC.55.al1; CPC.53; Cst.29.al2; CO.264.al1; CO.264.al2; CC.2.al2